Dual-Polarized Crossed Bowtie Dipole Array for Wireless Communication Applications - Zhi-Ya Zhang; Shuang Li; Shao-Li Zuo; Jia-Yue Zhao; Xiao-dong Yang; Guang Fu (International Journal of Antennas and Propagation)
A dual-polarized array with downtilted radiation patterns is proposed for wireless communication applications. The proposed dual-polarized antenna element achieves an enhanced impedance bandwidth and compact dimensions by introducing a parasitic circular patch and vertical metal cylinders, which is a good candidate for radiating elements in base station antennas. By optimizing the amplitude and phase distribution along the feed, a radiation pattern with a downtilted angle is obtained. The dual-polarized array antenna achieves an impedance bandwidth for VSWR ≤ 1.5, covering the frequency bands for 3G/LTE systems. Moreover, the proposed array achieves high port isolation, the stable antenna gain over the entire operating band. Therefore, the proposed array antenna is very suitable for potential wireless communication applications. A prototype has been manufactured and measured. The measurements, that match the design objectives, are also presented.